Public Value of the SAKTI Service Program at the Department of Population and Civil Registration of Kediri City - Ahmad Fauzi; Kalvin Edo Wahyudi; Tukiman (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
This study aims to analyze the public value of the SAKTI Program (Population Administration System Based on Information Technology) at the Department of Population and Civil Registration of Kediri City. The SAKTI Program is a digital-based population administration service innovation developed to provide convenience, speed, and efficiency in public services. This research used a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation. The analysis employed the public value theory proposed by Faulkner and Kaufman (2017), consisting of four dimensions: outcome achievement, trust and legitimacy, service delivery quality, and efficiency. The findings indicate that the SAKTI service has generated economic value through saving costs, time, and effort for the community, while also encouraging changes in public behavior toward the use of digital services. The SAKTI Program has also demonstrated strong legitimacy through clear legal foundations. However, public trust in digital services has not been fully established due to limited socialization and low digital literacy among some community groups. The quality of service delivery shows simplified procedures and easier access to services, although technical problems such as system disruptions and service delays are still encountered. In terms of efficiency, the SAKTI service has improved internal service efficiency, although the benefits have not been equally experienced by all members of society. Therefore, optimizing the SAKTI service requires improvements in system stability, wider socialization, and enhancement of community digital literacy.